The Psychological and Social Trauma of the Children in the Agrarian Conflict in Indonesia - Ratna Damayanti; Lubis, Amany; Ichsan Malik; Yusuf Ali; Agung Wibowo; Agus Adriyanto (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Land conflicts are still a major problem in Indonesia. The study on this paper examined the impact of agrarian conflicts through the children in Indonesia. Agrarian conflicts were not only impact to the landowners, but also have a significant impact on the children who were living in conflict areas. The study attempted the answer how children are involved in agrarian conflicts by highlighting the field context in agrarian conflicts, including psychological, social, and economic impacts? The methodology applied in this study was the qualitative method, with a literature review or desk review approachs and uses the conflict data collection system developed by the HuMa NGO, https://humawin.huma.or.id. This study found the trauma in psychological and social trauma to the children in agrarian conflict areas. This study provided comprehensive recommendations to protect and support children affected by agrarian conflicts in Indonesia with the meaningful participation of all multi-stakeholders or parties in the agrarian conflict.